Effects of metal foam meshes on premixed methane-air flame propagation in the closed duct. (May 2017) - Chen, Peng; Huang, Fujun; Sun, Yongduo; Chen, Xuexi
Abstract: In many practical applications, the comprehensive measures are needed to suppress the gas explosions, and lining the channel walls with porous materials before a special installation for flame résistance is an effective choice. The aim of the present work is to investigate the effect of porous materials on the premixed flame propagation process in a closed combustion tube. Experiments are carried out to examine the flame dynamics for the stoichiometric methane/air mixtures both in the empty tube and in the presence of porous materials. The results demonstrate that the flame propagation can be divided into five typical stages, and a tri-tulip flame is observed during the development of the classic tulip flame. The inversion distance L of the flame front is selected to characterize the tulip flame evolution. It is worth to notice that the flame tip fronts travel faster with smaller porous densities PPI(pores per inch) from the finger shape stages to flat shape stages. The explosion severity parameters, including peak pressure and maximum pressure growth rates, are compared for all configurations, and the porous density plays an important role on the explosion severity. The maximum rate of pressure rise decreases linearly with the porous densities. It is deduced that the metal foam meshes with the larger porous densities PPI have more significant impacts on suppressing the tulip formation. The coupling of the flame front with the pressure wave plays a significant role in the onset and evolution of the tulip flame. As a whole, the metal foam meshes can reduce the overpressures can reduce the overpressures by33.3%–46.6%, while they have little effect on the flame tip speeds and shapes. Highlights: A tri-tulip is found during the development of the classic tulip flame. As a whole, the metal foams can reduce the overpressures by 33.3%–44.6%. The coupling of the flame front with the pressure wave plays an important role in the onset and evolution of the tulip flame.